The value of spectral imaging to reduce artefacts in the body after 125I seed implantation. Issue 5 (9th September 2016) - Liu, Jingang; Wang, Wenjuan; Zhao, Xingsheng; Shen, Zhen; Shao, Weiguang; Wang, Xizhen; Li, Lixin; Wang, Bin
Abstract: Introduction: To explore the value of gemstone spectral imaging (GSI) and metal artefact reduction sequence (MARs) to reduce the artefacts of metal seeds. Methods: Thirty‐five patients with 125 I seed implantation in their abdomens underwent GSI CT. Six types of monochromatic images and the corresponding MARs images at 60–110 keV (interval of 10 keV) were reconstructed. The differences in the quality of the images of three imaging methods were subjectively assessed by three radiologists. Length of artefacts, the CT value and noise value of tissue adjacent to 125 I seeds, contrast‐to‐noise ratio (CNR), and artefact index (AI) were recorded. Results: The differences in subjective scoring were statistically significant ( t = 10.87, P < 0.001). Images at 70 keV showed the best CNR (0.84 ± 0.17) of tissues adjacent to 125 I seeds, and received the highest subjective score (2.82 ± 0.18). Images at 80 keV had the lowest AI (70.67 ± 19.17). Images at 110 keV had the shortest artefact lengths. High‐density metal artefacts in the MARs spectral images were reduced. The length of metal artefacts in images at 110 keV was shorter than that of the polychromatic images and MARs spectral images ( t = 3.35, 3.89, P < 0.05). The difference in CNR between MARs spectral images and polychromatic images, and images at 70 keV was statistically significant ( t = 3.57, 4.16, P < 0.01). Conclusions: Gemstone spectral imaging technique can reduce metal artefacts of 125 I seeds effectively in CT images, and improve the quality of images, and improve the display of tissues adjacent to 125 I seeds after implantation. MARs technique cannot reduce the artefacts caused by radioactive seeds effectively.